Controlling morphologies and growth mechanism of hexagonal prisms with planar and pyramid tips of ZnO microflowers by microwave radiation - Phuruangrat A. (Elsevier Ltd, 2014)
Flower-like ZnO microstructures of hexagonal prisms with planar and hexagonal pyramid tips were successfully synthesized by a microwave radiation method. The precursor solutions were synthesized from zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and hexamethylenetetramine (HMT) at pH 9 and 13. The as-synthesized products were pure hexagonal wurtzite ZnO microstructured flowers of hexagonal prisms with planar tips at pH 9 and of hexagonal prisms with hexagonal pyramid tips at pH 13. Sharp and strong optical phonon Raman-active mode of E2H was detected at 438 cm-1. The excitonic characters of the absorption peaks were also detected at 397 nm for the first product and 384 nm for the second one, and the decolorization efficiency of RhB by Hg-lamp irradiation for 140 min was 77% and 87%, respectively. © 2014 Elsevier Ltd and Techna Group S.r.l.